Freshwater blue-green continental algae of the province of La Pampa (Semiárida, 2020)
This paper represents our first contribution to the study of blue-green continental algae from La Pampa Province; we have identified 38 species including varietes, from which 4 taxa Coelosphaerium confertum, Merismopedia marsonii, Oscillatoria curviceps var. angusta and Cylindrospermum alatosporum, represent new records for Argentina, while 33 are cited for the first time in our province.
Keywords: Blue-green algae; Systematic